Application of Fragment-Based Drug Discovery to Versatile Targets - Li, Qingxin (Frontiers in Molecular Biosciences, 2020)
Fragment-based drug discovery (FBDD) is a powerful method to develop potent small-molecule compounds starting from fragments with binding weakly to targets. As FBDD exhibits several advantages over high-throughput screening campaigns, it becomes an attractive strategy in target-based drug discovery. Many potent compounds/inhibitors of diverse targets have been developed using this approach. Methods used in fragment screening and understanding fragment-binding modes are critical in FBDD. This review elucidates fragment libraries, methods utilized in fragment identification/confirmation, strategies applied in growing the identified fragments into drug-like lead compounds and applications of FBDD to different targets. As FBDD can be readily carried out through different biophysical and computer-based methods, it will play more important roles in drug discovery.